2022
DOI: 10.3390/ijerph192214838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Digital Economy Development on Carbon Emission Efficiency: A Spatial Econometric Analysis Based on Chinese Provinces and Cities

Abstract: In the realistic context of the development of China’s digital economy and carbon peaking and carbon neutrality goals, to efficiently achieve high-quality economic and green and low-carbon transformation, this paper investigates the impact of digital economy development on the carbon emission efficiency of 30 Chinese provinces and cities from 2011–2019. In this paper, firstly, the digital economy development index and carbon emission efficiency are calculated by the entropy method and the Super-SBM-Undesirable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…A large employment population attracts a concentration of laborintensive industries, which can bring about problems such as a decrease in environmental air quality, while promoting economic development. Therefore, we chose year-end employment as a labor input [56,57]. (iii) The crucial aspect in developing a low-carbon economy is saving energy without curtailing economic output.…”
Section: Estimation Of Co 2 Emissions Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…A large employment population attracts a concentration of laborintensive industries, which can bring about problems such as a decrease in environmental air quality, while promoting economic development. Therefore, we chose year-end employment as a labor input [56,57]. (iii) The crucial aspect in developing a low-carbon economy is saving energy without curtailing economic output.…”
Section: Estimation Of Co 2 Emissions Efficiencymentioning
confidence: 99%
“…Therefore, we used science and technology expenditure as a measure of municipalities' technology inputs. (v) GDP (converted to constant 2000 prices) reflects the overall level of municipal economic development [56][57][58]. Retail sales of social consumer goods reflect the material living standards of citizens and the purchasing power of social goods.…”
Section: Estimation Of Co 2 Emissions Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that there is an inverted U-shaped relationship between the digital economy and carbon dioxide emissions in cities; i.e., the digital economy first increased carbon dioxide emissions and then reduced carbon emissions. Liu et al (2022) [23] researched the impact of digital economy development on carbon emission efficiency based on Chinese 30 provinces and cities. Yan et al (2020) [24] tested the heterogeneous relationship between the PM 2.5 level and the economy using two-step quantile panel regression.…”
Section: Introductionmentioning
confidence: 99%
“…As a new driving force of economic development, technological improvement, employment security and other aspects, digital economy has received extensive attention from scholars. It has a strong resource integration capability and technological selection effect, and can help to improve information asymmetry and resource efficiency through environmental monitoring, information mutual assistance, industrial structure optimization and other ways to help green technological innovation research, development and utilization, thus promoting coordinated promotion between ACE reduction and APS guarantee [26][27][28]. In essence, the coordinated promotion between ACE reduction and APS guarantee is to ensure the efficient unity of environmental protection and economic growth.…”
Section: Introductionmentioning
confidence: 99%